ChemInform Abstract: Bismuth Based Hybrid Perovskites A3Bi2I9 (A: Methylammonium or Cesium) for Solar Cell Application. Issue 5 (January 2016) - Park, Byung‐Wook; Philippe, bertrand; Zhang, Xiaoliang; Rensmo, Hakan; Boschloo, Gerrit; Johansson, Erik M. J.
Abstract: In view of the possible replacement of toxic lead perovskites in solar cells by a less toxic electrode material, Bi‐based perovskites A3 Bi2 I9 (A: MeNH3, Cs) are synthesized by reaction of metallic Cs or MeNH3 I with BiI3 in a 7:3 DMF/DMSO mixture.